Speech and brain-mechanisms - Penfield, Wilder, 1891-1976; Roberts, Lamar (Princeton legacy library., 1959)
The outcome of ten years' work, this book is a carefully planned study of brain dominance, aphasia, and other speech disturbances, and includes a discussion of the cerebral mechanisms of speech and the learning and teaching of language. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback e.